Ethnobotany of Stem Bark of Certain Plants of Visakhapatnam District, Andhra Pradesh - and O. Aniel Kumar, J. Koteswara Rao*, T.V.V. Seetharami (Current Botany, 2011)
The paper enumerates 56 medicinal plant species belonging to 47 genera and 31 families, whose stem barks are used for ethnobotanical purposes by the Primitive Tribal Groups (PTGs) of Visakhapatnam district, Andhra Pradesh. Three plant species and 70 practices were found to be new.